Additive combinatorics - Tao, Terence, 1975- (Cambridge studies in advanced mathematics, 2006)
For the first time, the many different tools from different fields that are used in additive combinatorics are brought together in a self-contained and systematic manner. This graduate level textbook will quickly allow students and researchers easy entry into the fascinating field of additive combinatorics.